Constitutional control in Eastern European countries: models, effectiveness and development prospects - Lysak, Karolina; Voichuk, Alina; Okuniev, Ihor; Pustovar, Vladyslav; Nastasiak, Iryna; Окунєв, Ігор Сергійович (Observare, 2025)
This study provides a systematic analysis of the effectiveness of constitutional control in Eastern Europe in order to identify mechanisms of democratic degradation and preventive safeguards, given the rule-of-law crises observed in several states. The objective is to examine models, performance, and development prospects of constitutional review through the lens of checks and balances, based on the activities of constitutional courts in Estonia, Latvia, Lithuania, Poland, the Czech Republic, Slovakia, Hungary, and Ukraine during 2015– 2024. The methodology includes functional analysis of three core roles of constitutional courts (protection of fundamental rights, arbitration between branches of power, and constitutional interpretation), case-study analysis of four constitutional crises (Poland 2015–2023, Hungary 2010–2025, Romania 2012–2024, Ukraine 2010–2025), and correlation analysis using data from the World Justice Project, V-Dem Judicial Independence Index, official court reports, and Venice Commission conclusions. The results identify three distinct functional models: (1) Full constitutional arbitration (Baltic states, Czech Republic) with high efficiency indicators; (2) Selective control under political pressure (Poland, Hungary) with sharp declines in performance after political interference; (3) Unstable control (Ukraine, Romania, Bulgaria) marked by high variability. The study demonstrates increasing divergence among models from 2015 to 2024, with the standard deviation of the composite efficiency index rising from 12.4 to 19.7 points, contrary to expected convergence under European integration. The analysis also reveals common techniques of political capture of constitutional justice (procedural manipulation, court-packing, and reinterpretation of constitutional norms). Correlation results show strong links between judicial independence and appointment mechanisms, with higher efficiency associated with transparent selection procedures and balanced institutional design. © 2026, Observare. All rights reserved.
Keywords: Constitutional Control; constitutional courts; democratic rollback; Eastern Europe; System Of Checks and balances